Pengetahuan Ibu Dan Pemberian Asi Eksklusif Dengan Kejadian Stunting Pada Balita 2-5 Tahun Di Puskesmas Kawangkoan Minahasa - Grace K.L. Langi; I Made Djendra; Rudolf B. Purba; Ryan S.P. Todanggene (POLTEKKES KEMENKES MANADO, 2019)
Nutrition is an important part of growth and development, because there is a connection and is related to health and intelligence, malnutrition. Stunting is a linear growth disorder that can affect the increased risk of illness, death, and impaired late motor development, and stunted mental growth. The type of this research is analytic observational with cross sectional study approach. The population in this study were all children under five in the work area of Kawangkoan Health Center in Minahasa Regency. Children under five 2-5 years. The respondent is mother. The number of samples of this study amounted to 41 people with a sampling technique that is using simple random sampling technique. The results of research on the level of maternal knowledge of 41 respondents were 39.0% who lacked knowledge, and 41.5% had sufficient knowledge, while 19.5% had good knowledge. the rate of exclusive breastfeeding is 41.5% which is less than exclusive breastfeeding, while 39.0% is good, 19.5% is enough to provide exclusive breastfeeding. Toddler respondents who have normal height category are 46%, and category is very short, 31.7%, while the short category is 22.0%. kawangkoan health center.